Emergency nursing care with a medical diagnosis of fracture in the surgical emergency departement of Dr. Wahidin sudirohusodo hospital, makassar - Abd. Malik; Mikawati (Diagnosa, 2025)
Background: Fractures are one of the cases frequently encountered in the Emergency Department, especially due to traffic accidents. This condition not only causes damage to the bone, but also presents nursing problems such as severe pain, limited movement, risk of shock, and infection (Smeltzer, 2017). (WHO, Road traffic injuries – Fact sheet, 2023)reported that traffic accidents are still the main cause of the increasing number of fractures and contribute significantly in developing countries. Purpose: This case study aims to describe the nursing care process for fracture patients in the Emergency Department of Dr. Wahidin Sudirohusodo General Hospital, Makassar. Methods: This case study uses a descriptive method by systematically presenting the case and applying a nursing process approach. The main focus is directed at one of the priority issues that emerged in the case, namely providing nursing care to a client with a fracture. Results: The nursing care provided to patient Mr. G revealed acute pain, impaired mobility, risk of shock, and risk of infection. Meanwhile, patient Mr. D experienced acute pain, impaired mobility, and risk of infection. Nursing actions provided included pain management, mobilization support, shock prevention, and wound care. Conclusion: The discussion demonstrates a congruence between theory and practice, particularly in pain management and mobility. Nursing care plays a crucial role in stabilizing the patient's condition before further medical intervention. In conclusion, care for fracture patients in the emergency department (ED) should focus on pain control, complication prevention, and emotional support for the patient and family. Nurses are advised to improve their skills in pain management and shock management, while hospitals are encouraged to strengthen emergency facilities and emergency training.